World Heritage craze in China universal discourse, national culture and local memory - Yan, Haiming (Berghahn Books, 2018)
There is a World Heritage Craze in China. China claims to have the longest continuous civilization in the world and is seeking recognition from UNESCO. This book explores three dimensions of the UNESCO World Heritage initiative with particular relevance for China: the universal agenda, the national practices, and the local responses. With a sociological lens, this book offers comprehensive insights into World Heritage, as well as China's deep social, cultural, and political structures
Keywords: Geschichte; Weltkulturerbe; China; World Heritage areas / China